2010
DOI: 10.1007/s11250-010-9700-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of B5R gene of zoonotic buffalo pox virus isolates with other orthopoxviruses

Abstract: The present paper describes the isolation of buffalo pox virus from scab lesions and its molecular characterization through B5R gene sequencing. During our study, pustular pox lesions were observed on the teats and mammary parenchyma of cattle and buffaloes, and the disease was of significant zoonotic importance since similar lesions were produced on the hands, legs, and face of people in close contact with the affected animals. The collected scab materials were subjected for virus isolation in 9-11-day-old ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Buffalopox is endemic with increasing trend in India (Prabhu et al, 2012) and outbreaks are reported from Maharashtra, Gujarat, Rajasthan, Andhra Pradesh, Tamilnadu and Karnataka states in India (Figure 3) Bhanuprakash et al, 2010c;Chandranaik et al, 2011;Gurav et al, 2011). Apart from Egypt, India, it is also been reported from several other countries namely Italy, Russia, Pakistan, Indonesia, Bangladesh and Nepal .…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Buffalopox is endemic with increasing trend in India (Prabhu et al, 2012) and outbreaks are reported from Maharashtra, Gujarat, Rajasthan, Andhra Pradesh, Tamilnadu and Karnataka states in India (Figure 3) Bhanuprakash et al, 2010c;Chandranaik et al, 2011;Gurav et al, 2011). Apart from Egypt, India, it is also been reported from several other countries namely Italy, Russia, Pakistan, Indonesia, Bangladesh and Nepal .…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Buffalopox virus (BPXV), a variant of vaccinia virus, is associated with severe disease outbreaks among buffaloes and cattle . The disease also occurs in humans in close contact with BPXV affected animals . In recent years, infection because of vaccinia and vaccinia‐like Contagalo and Aracatuba viruses has been reported from South American counties .…”
mentioning
confidence: 99%
“…Scab lesions collected from ailing farmers and buffaloes for laboratory investigations were processed and inoculated separately in 9‐day‐old chick embryos by chorio‐allontoic membrane (CAM) route and on to confluent monolayer of Vero cells as per previously described procedures . Characteristic pock lesions on CAM of chicken embryos (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Молекулярно-биологическая оценка выделенных за последние 20 лет от человека и буйволов изолятов показала, что все они относятся к вирусу оспы буйволов. Важно отметить, что все штаммы вируса оспы буйволов, выделенные на территории Индии, практически не различаются, но отличаются от изолированных в других странах, кроме штамма Hyderabad: различия для ATIгена составляют 0,3% [30,31].…”
unclassified